Les nouveaux bostan d’Istanbul : quelle pérennisation pour les jardins de la contestation ? - Agathe Fautras (European Journal of Turkish Studies)
Following the May-June 2013 Gezi Park protests in Istanbul comprising occupy Taksim Square and the nearby Gezi Park, protestors and local inhabitants have created bostan (“vegetable gardens”) in the interstices of urban space without consulting the municipality. Their aims have been to combat urban spread and to raise awareness of political and ecological claims, thereby prolonging the energy and the ideals of the Gezi movement. Nevertheless, their informal and protesting nature raises the question of the perpetuation of such initiatives. Discussion turns to the form of “nature” that should exist in the city, the integration of these territories into the local neighborhoods and the institutionalization of these spaces.